Multimodality imaging in connective tissue disease-related interstitial lung disease. Issue 2 (February 2021) - Ruano, C.A.; Grafino, M.; Borba, A.; Pinheiro, S.; Fernandes, O.; Silva, S.C.; Bilhim, T.; Moraes-Fontes, M.F.; Irion, K.L.
Abstract : Interstitial lung disease is a well-recognised manifestation and a major cause of morbidity and mortality in patients with connective tissue diseases. Interstitial lung disease may arise in the context of an established connective tissue disease or be the initial manifestation of an otherwise occult autoimmune disorder. Early detection and characterisation are paramount for adequate patient management and require a multidisciplinary approach, in which imaging plays a vital role. Computed tomography is currently the imaging method of choice; however, other imaging techniques have recently been investigated, namely ultrasound, magnetic resonance imaging, and positron-emission tomography, with promising results. The aim of this review is to describe the imaging findings of connective tissue disease-related interstitial lung disease and explain the role of each imaging technique in diagnosis and disease characterisation.